The increasing risk of temporomandibular disorder and articular eminence inclination due to tooth loss - Chairunnisa, Ricca; Harahap, Rahmadhani (Padjadjaran Journal of Dentistry, 2022)
ABSTRACTIntroduction: Tooth loss leads to increased biomechanical pressure in the temporomandibular joint due  to changes in the functional movement pattern of the jaw, resulting in joint structure damage specifically  change of the articular eminence inclination (AEI) angle, which is one of the increased risks of the  temporomandibular disorder (TMD). This study aimed to analyze the relationship between the number  and quadrants of tooth loss on TMD and the AEI. Methods: It was descriptive-analytic study using a cross sectional design. The study was done in Universitas Sumatera Utara (USU) Dental hospital, conducted  questionnaires and panoramic radiographic on 42 subjects aged over 18-64 years with tooth loss. Data  analyzed used Chi-square analysis. Results: The prevalence of TMD on the ≥3 tooth loss group by 82.6%  and the four-quadrant group by 93.8%. The prevalence of change in the AEI on the ≥3 tooth loss group  was 34.8% on the flat right side, while on the left side of 26.1% was flat, and 13% was steep. Based on the  number of quadrants tooth loss, the highest was on the four-quadrant group by 50% on flat right side, and  on the three-quadrant group was 25% flat, 25% steep on the left side. There was a significant relationship  between the number of tooth loss (p=0.023), the number of tooth loss quadrants, and TMD (p=0.016).  There was no relationship between the number of tooth loss and the AEI, except for the number of tooth  loss quadrants and the AEI on the right side with a significant result (p=0.017). Conclusion: There was  relationship between the number of tooth loss, the number of tooth loss quadrants, and TMD and there  was no relationship between the number of tooth loss and the AEI, except for the number of tooth loss  quadrants and the AEI on the right side.Keywords: Edentulous; tooth loss; temporomandibular disorder; inclination of articular eminence.